Mixed findings on service recovery paradox: An illustration from An experimental study - Ok, Chihyung; Back, Ki-Joon; Shanklin, Carol W. (My University, 2008)
The purpose of this study was to test the service recovery paradox and double deviation on customers' overall satisfaction considering definitional and methodological issues. This study employed a scenario experimentation manipulated three dimensions of justice at two levels each ( 2 x 2 x 2 factorial design). A convenience sample of 286 casual restaurant customers was used in the study. Paired sample t-tests were employed to test recovery paradox and double deviation effects after selecting four groups of customers based on recovery satisfaction to take into account the if-condition in the definition of the service recovery paradox. Customers' post-recovery overall satisfaction could be higher than their initial overall satisfaction provided customers were highly satisfied with service recovery ( recovery paradox). When customers are somewhat satisfied with recovery efforts, their initial overall satisfaction could be carried over after two transactional evaluations. Double deviation effects were obvious and consistent when customers were either highly dissatisfied or somewhat dissatisfied with service recovery.
Keywords: Service failure; Satisfaction; Service Recovery Paradox; Double deviation; Ceiling effect